Manajemen sumber daya manusia dalam meningkatkan daya saing sekolah di SDS Al-Huffazh Kota Payakumbuh - Muhammad Ridho,; Ilmi, Darul; Zakir, Supratman; Dewi, Yelfi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The success of an educational institution or organization is strongly influenced by human resource management. When human resources are professionally managed, it affects the progress of the institution or organization, but if it is not properly managed, then it can lead to setbacks in the educational institution. Al Huffazh Elementary School, which is located in Payakumbuh City, has attained several excellent hallmarks, such as achievements in the academic and non-academic fields, the optimum number of teachers and staff, excellent religiousbased services, established memorization targets for students with 3 juz to Standard VI, excellent extra-curricular activities and won various national level competitions. This study aims to analyze and explore the human resource management system implemented in this school in order to augment the school’s competitiveness and engineer several impactful outcomes, one being to establish a very high level of community satisfaction and trust in Al-Huffazh Elementary School, Payakumbuh. This qualitative study used a descriptive approach. The findings of the study indicate that the recruitment of teachers and school employees was carried out professionally in several stages according to the prescribed regulations, performance of teachers and employees is continuously improving and developed through various types of training. In addition, the performance of teachers and employees is periodically measured.